Organizational Performance and Chief Executive Officer’s (CEO’s) Compensation for Firms Listed in Nairobi Securities Exchange, Kenya - Anne, Omamo; K’obonyo, Peter; Muindi, Florence (European Scientific Journal, ESJ, 2020)
This study examined the link between organizational performance and CEO’S compensation of firms listed at the NSE. Past studies on the determinants of CEO’S compensation revealed a lack of consensus to the explanation of increases in CEO’S compensation. While most of the studies confirm linkages between organizational performance and CEO’S compensation, they measured organizational performance using financial indicators of performance, the current study investigates the relationship between organizational performance and CEO’S compensation but differs from the previous studies by expanding the measures of organizational performance to include the balanced scorecard measures of performance. The theoretical foundations of this study were based on agency theory. The study’s population constituted 60 firms listed at the NSE. Descriptive crossectional survey was adopted for this study. Both Primary and Secondary data were used to gather information required for the study. Descriptive statistics and regression were used to analyze and interpret the collected data. The study revealed that there wassignificant and positive relationship between organizational performance and CEO’S compensation. The findings of this study are of benefit to board members of organizations in identifying the performance measures that are important to consider when making decisions on CEO’S compensation.